Trend of Biotechnology Applications in Pest Management: A Review - Alemu, Melaku (International Journal of Applied Sciences and Biotechnology, 2020)
There are many constraints that severely affect the global agricultural production and productivity which include the ever increasing of population growth, degradation of natural resources, climate changes and emerging pests. Among these factors, biotic constraints or pests are known to cause 25-50% or complete loss of plant production. Accordingly, various plant protection technologies have been deployed with the trend of focusing on the use modern biotechnological tools that are proven to be most effective and mandatory. The review covers a wide array of pest management methods ranging from the conventional biological control methods up to molecular breeding techniques. Furthermore, the application of new genetic engineering techniques fueled by new breakthroughs and innovations are the cornerstone of this review. Accordingly, the continuous increasing trend of GM crops cultivation in both crop type and hectare has urged many countries to deploy the technology as a key strategy to enhance their bioeconomy. In fact, plant protection is the discipline that immensely benefit from biotechnology than any other disciplines for ensuring food security and sustainable development. However, in order to fully exploit the enormous potential of biotechnology, appropriate biosafety regulatory frameworks and proper stewardship programs need to be effectively implemented. This integrated approach can promptly help respond to the ever-dynamic threat of pests and hence reliably combat food insecurity and ably contribute to sustainable development. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 108-131